2007
DOI: 10.1158/0008-5472.can-07-0986
|View full text |Cite
|
Sign up to set email alerts
|

16-kDa Prolactin Inhibits Endothelial Cell Migration by Down-Regulating the Ras-Tiam1-Rac1-Pak1 Signaling Pathway

Abstract: Angiogenesis plays a key role in promoting tumorigenesis and metastasis. The 16-kDa fragment of prolactin (16k PRL) is an NH 2 -terminal natural breakdown fragment of the intact 23-kDa prolactin and has been shown to have potent antiangiogenic and antitumor activities. The mechanism(s) involved in the action of 16k PRL in endothelial cells remains unclear. In this study, we showed that 16k PRL reduced rat aortic endothelial cell (RAEC) migration in a wound-healing assay and in a Matrigel tube formation assay, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 53 publications
2
40
0
2
Order By: Relevance
“…Similarly, we found that Wnt protein is able to induce PAK1 activation in HEK293T cells and endogenous PAK1 activity is partially required for full b-catenin accumulation in both HEK293T and mouse L-cells upon Wnt stimulation. In colon cancer cells, signaling from K-Ras/Rac1 (Lee et al, 2007;Wang et al, 2010b), IGF (Sun et al, 2009) or EGF (Galisteo et al, 1996;Lu et al, 1997) pathways all may induce PAK1 activation, which maintains the high phosphorylation state of b-catenin S675.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found that Wnt protein is able to induce PAK1 activation in HEK293T cells and endogenous PAK1 activity is partially required for full b-catenin accumulation in both HEK293T and mouse L-cells upon Wnt stimulation. In colon cancer cells, signaling from K-Ras/Rac1 (Lee et al, 2007;Wang et al, 2010b), IGF (Sun et al, 2009) or EGF (Galisteo et al, 1996;Lu et al, 1997) pathways all may induce PAK1 activation, which maintains the high phosphorylation state of b-catenin S675.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 is required for activation of hypoxia inducible factor 1 (Hirota et al, 2001). Rac1 is also necessary for the induction of VEGFR-2 in vascular endothelial cells (Meissner et al, 2009) and is necessary for endothelial cell migration (Lee et al, 2007). VEGF activates Rac1 via vav-2 (Garrett et al, 2007) and activation of Rac1 is involved in the hypoxia-induced production of angiogenesis-promoting factors (Xue et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This assay was performed as recommended by earlier research (24,50). Briefly, each well of the 96-well plates was precoated with 50 l of Matrigel (BD Biosciences, Bedford, MA) and allowed to polymerize for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%